ANALISIS PENGARUH GAYA GEMPA TIDAK SERAGAM TERHADAP RESPONS STRUKTUR JEMBATAN GANTUNG - Sari, Putri Kumala; Fransiska, Yolla (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2025)
Bridges are essential infrastructures that serve to connect two regions separated by various geographical conditions. Among the various types of bridges, suspension bridges are commonly used for long-span applications. The main structural components of a suspension bridge consist of the main cables and vertical suspenders. Due to their long spans, suspension bridges are susceptible to differential ground motions at each support, which may arise from varying soil conditions—this phenomenon is referred to as multi-support excitation. In this study, three types of analyses were conducted: static analysis, dynamic analysis under longitudinal seismic excitation, and dynamic analysis under transverse seismic excitation, using MIDAS Civil software. The soil conditions applied in all three analyses were assumed to be stiff soil at the left support and soft soil at the right support. The structural responses observed include internal forces and displacements. The seismic loads were defined using the time history method. The time history records were derived from the conversion of response spectra for the Bukittinggi region, considering both stiff and soft soil conditions. The results indicate that, in both longitudinal and transverse dynamic seismic analyses, the highest internal force values predominantly occurred at the support located in the soft soil area, except for moment values, which reached their maximum at the support in the stiff soil area. The maximum Dynamic Amplification Factor (DAF) in the longitudinal direction of the girder occurred at an element located at 0,25 of the span length on the right side, with a value of 2,621.